Equinodermos de Nicaragua: nuevos registros del Pacífico y Caribe Sur - Sandino, Osmar Benito (2017)
Abstract: Echinoderms from Nicaragua: new records for the Pacific and South Caribbean. There is little information about the echinoderms of Nicaragua. Here we present a list based on bibliographical revisions and collections of specimens made in the last three years. Samplings were made from June 11 to 16, 2016, in 10 locations (two in the Pacific and eight in the Caribbean). In addition, the databases of eight international scientific collections were reviewed. Finally, reports were added from photographic archives of the school of diving Dive Nicaragua and ECOLÓGICA S.A. The list of echinoderms of Nicaragua consists of 193 species distributed in five classes, 112 genera, 58 families and 24 orders. The class with the highest number of species was Asteroidea (57 species), followed by the class Echinoidea (46 species), and the class with the lowest number of species was Crinoidea (10 species). Fifty six new records are added for Nicaragua, 19 of which correspond to the Pacific and 38 to the Caribbean. Rev. Biol. Trop. 65(Suppl. 1): S288-S298. Epub 2017 November 01.